Respon Pertumbuhan Tanaman Sawi Dengan Memanfaatkan Limbah Cair Ampas Tahu Sebagai Pupuk Organik - Lawalata, Jacob J.; Merahabi, Paskalius Apriyanto; Linggi, Mery I.; Indey, Elisabet (STIPER Santo Thomas Aquinas Jayapura, 2025)
The purpose of this study was to obtain information about the effect of tofu dregs liquid waste on the growth of mustard greens. The study was conducted in Pobaim Village, Jayapura Regency Regency, for 1 month, namely, in July 2024. This study used a Randomized Block Design (RAK) (Peterson, 1994), with 6 treatments of tofu dregs liquid waste, namely, control (AT0), 100 ml of dregs liquid waste per 1 liter of water (AT1), 150 ml of dregs liquid waste per 1 liter of water (AT2), 200 ml of dregs liquid waste per 1 liter of water (AT3), 250 ml of dregs liquid waste per 1 liter of water (AT4) and 300 ml of dregs liquid waste per 1 liter of water (AT5). The treatment was repeated three times so that there were 18 experimental units. The observation variables that will be carried out in this study are plant height, number of leaves, leaf width, leaf length, and root length. The results of this study did not have a significant effect on all observed variables.